PERLINDUNGAN KONSUMEN TERHADAP PENGGUNA APLIKASI TIKTOK CASH DI MEDIA SOSIAL - Yusep Mulyana (Journal of Innovation Research and Knowledge, 2023)
The regulation of users of the TikTok Cash application is regulated in laws and regulations, which are stated in Article 4 of Law Number 8 of 1999 concerning Consumer Protection, where in this aspect of consumer protection, users of the TikTok Cash application must obtain their rights, some rights are not fulfilled in the use the TikTok Cash application, namely, the right of consumers to get maximum service, the right to receive correct, clear, and honest information about the conditions and guarantees of goods and/or services from a product offered, the right of users to be treated fairly or served honestly and not discriminatory rights, the right to obtain compensation, compensation and/or replacement, if the product received is not in accordance with the agreement or not as it should be. Settlement of consumer disputes in electronic transactions that occur in Indonesia. Dispute resolution over the use of the TikTok Cash application can be resolved through non-litigation (not through court) with Alternative Dispute Resolution efforts in the form of Consultation and Negotiation, but if a solution is still not found, then you can take litigation (through the courts) even though settlement through litigation institutions is considered insufficient. efficient in terms of time, cost, and effort, but the results of problem solving will be very effective in restoring rights for losses incurred for users of the TikTok Cash application.